Effect of Volume in Resistance Training on Inhibitory Control in Young Adults: A Randomized and Crossover Investigation - Leonardo de Sousa Fortes; Manoel da Cunha Costa; Raphael José Perrier-Melo; Jorge Luís Brito-Gomes; José Roberto Andrade Nascimento-Júnior; Dalton Roberto Alves Araújo de Lima-Júnior; Edilson Serpeloni Cyrino (Frontiers in Psychology, 2018)
Purpose: The aim of the study is to compare the effect of resistance training volume on inhibitory control in young adults with previous experience in resistance training.Method: All the 27 participants underwent 40-week experiment, divided in three training phases of 8-week duration. A washout period of 8 weeks between each of the training phases was carried out. The participants performed 1, 3, or 5 sets of the same exercises with equalized intensity (loading zones) and rest. Inhibitory control was assessed by the Stroop Test.Results: Interaction effect was found for inhibitory control accuracy [F(5,22) = 56.88, p < 0.01] and mean response time [F(5,22) = 83.02, p < 0.01] for 3 sets (p = 0.01; ES = 0.6) and 5 sets (p = 0.01; ES = 0.8) when compared to 1 set.Conclusion: In conclusion, 1 set of resistance training may provide insufficient volume stimulus for positive adaptation in inhibitory control when compared to 3 or 5 sets.